2017
DOI: 10.18203/2320-1770.ijrcog20170579
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart rate patterns in patients with thick meconium staining of amniotic fluid and its association with perinatal outcome

Abstract: Background: This study assesses the role of abnormal fetal heart rate tracing patterns in patients with thick meconium staining of the amniotic fluid and its association with perinatal outcomes.Methods: Prospective unmatched case-control study on 2 groups of 136 subjects each- cases had thick MSAF and controls had clear liquor with abnormal fetal heart rate tracings on cardiotocography.Results: Gestational age (GA) >40 weeks, was found to have a significant association with MSAF (p value 0.01556 CI 95%). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 7 publications
(8 reference statements)
5
22
1
Order By: Relevance
“…18,19 Present study showed maximum cases i.e., 115(70%) with MSAF seen in gestational age ≥40 weeks, which was comparable with studies conducted by Mudhra R et al, having 50% incidence; Desai DS et al, giving an incidence of 63.96% and Fischer C et al, showing maximum cases seen in post-dated pregnancy respectively (Table 1). [20][21][22] Stage of labour at which the MSAF was diagnosed was in active stage with thin meconium (75.8%), which is comparable with study done by Qadir S et al, giving incidence of 70.37% (Table 1). 6 In present study the antenatal complications are more associated with thin meconium stained liquor compared to other deliveries with no meconium (Figure 1).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…18,19 Present study showed maximum cases i.e., 115(70%) with MSAF seen in gestational age ≥40 weeks, which was comparable with studies conducted by Mudhra R et al, having 50% incidence; Desai DS et al, giving an incidence of 63.96% and Fischer C et al, showing maximum cases seen in post-dated pregnancy respectively (Table 1). [20][21][22] Stage of labour at which the MSAF was diagnosed was in active stage with thin meconium (75.8%), which is comparable with study done by Qadir S et al, giving incidence of 70.37% (Table 1). 6 In present study the antenatal complications are more associated with thin meconium stained liquor compared to other deliveries with no meconium (Figure 1).…”
Section: Discussionsupporting
confidence: 85%
“…22,23 The cases with thick MSAF needed more of operative interference in the present study giving an incidence of 64.1%, whereas the incidence of vaginal delivery was more with thin MSAF 81(65.3%) showing stastical significance with p value of 0.001 ( Correlation of thick and thin MSAF with Apgar score at 1 and 5 min is statistically significant with p value of 0.003 and 0.001 respectively ( 6,20 But study done by Desai DS et al, showed that there was no much difference between Apgar at 1 and 5 minutes. 21 In the present study, there only 2 cases had meconium aspiration syndrome (MAS) with thick MSAF giving incidence of 5.1% showing statistical significance with p value of 0.011 (Table 2), which was similar to studies done by Desai D et al, and Priyadarshini MV having incidence of 6% and 5% respectively and low incidence of 2.01% in a study done by Akhila S et al 13,18,23 Thus, showing that the incidence of MAS is not directly associated with thin or thick MSAF. Neonates admitted to NICU for >24 hours were more with thick MSAF i.e., 33.3% with a p value of <0.001 showing high significance, which was similar to study done by Qadir S et al, having 46.7% of NICU admissions with thick MSAF.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, a significantly higher proportion of the fetuses showed non-reassuring fetal heart rate pattern (78.57% vs 55% p=0.002), low 5 min Apgar score (31.42% vs 15%) in group K when compared to group N. Similar findings were seen in the study done by Starks GC et al and Desai DS et al As thick meconium is particulate, when aspirated, it significantly increases fetal hypoxia which is reflected as non-reassuring fetal heart rate pattern. 5,14 The average birth weight in present study was 2.88 kg in group K and 2.94 kg in group N. Whereas in the study done by Yinka et al (3.43kg), the average birth weight was significantly higher compared to present study. This could be due to low average birth weight in Indian population compared to western countries.…”
Section: Discussioncontrasting
confidence: 61%
“…Similarly, in the study done by Desai DS et al and Patil Kamal et al, the incidence of cesarean section was high in group K (56.2% vs 18%). 14,15 The most common indication for cesarean section in their study was also fetal distress. The probable reason for this could be the great importance assumed by the meconium in many medico legal pursuits and also the unavailability of fetal scalp pH monitoring for further confirmation of fetal distress.…”
Section: Discussionmentioning
confidence: 90%
“…8 patients, in our study had a reactive CTG trace with meconium stained liquor which is similar to a study by Desai et al where 30% of cases of meconium stained liquor had reactive CTG trace. 12 Though meconium stained liquor has a significant association with abnormal CTG in our study, all parameters of a CTG may be normal despite the presence of meconium stained liquor. Therefore decision to deliver should be based on overall assessment and not merely on CTG trace.…”
Section: -7mentioning
confidence: 44%